Prioritization of laminate flooring selection criteria from experts' perspectives: a spherical fuzzy AHP-based model. (2nd November 2022) - Singer, Hilal; Özşahin, Şükrü
ABSTRACT: Laminate flooring selection is an important phase in the design and construction of a building. Owing to the subjectivity and conflicting factors, the fuzzy multicriteria decision-making technique can be used for handling the problem. In this study, it is aimed to prioritize laminate flooring selection criteria from experts' perspectives. Five main criteria and twenty subcriteria are determined with the help of experts. A three-level hierarchy is devised for comparisons. The spherical fuzzy analytic hierarchy process is used to determine the importance of each criterion. According to the results, 'safety and health properties' (29.0%) and 'durability properties' (20.6%) are the most significant main criteria. Furthermore, 'walking safety' (10.7%), 'free of harmful substances' (8.6%), and 'scratch resistance' (6.7%) are found as the most important subcriteria. The proposed approach presents a different view because it contributes to analyzing the key attributes of laminate flooring. The findings of this study will help building owners, architects, and designers in making informed choices.